BPPV: Comparison of the SémontPLUS With the Sémont Maneuver: A Prospective Randomized Trial - Strupp, Michael; Goldschagg, Nicolina; Vinck, Anne-Sophie; Bayer, Otmar; Vandenbroeck, Sebastian; Salerni, Lorenzo; Hennig, Anita; Obrist, Dominik; Mandalà, Marco (Frontiers in Neurology, 2021)
Objective: To compare the efficacy of the Sémont maneuver (SM) with the new “SémontPLUS maneuver” (SM+) in patients with posterior canal BPPV canalolithiasis (pcBPPVcan). Methods and Patients: In a prospective trinational (Germany, Italy, and Belgium) randomized trial, patients with pcBPPVcan were randomly assigned to SM or SM+; SM+ means overextension of the head by 60+° below earth horizontal line during the movement of the patient toward the affected side. The first maneuver was done by the physician, and the subsequent maneuvers by the patients 9 times/day on their own. Each morning the patient documented whether vertigo could be induced. The primary endpoints were: “How long (in days) does it take until no attacks can be induced?” and “What is the efficacy of a single SM/SM+?” Results: In the 194 patients analyzed (96 SM, 98 SM+), it took 2 days (median, range 1–21 days, mean 3.6 days) for recovery with SM and 1 day (median, range 1-8 days, mean 1.8 days) with SM+ (p = 0.001, Mann-Whitney U-test). There was no difference in the second primary endpoint (chi2-test, p = 0.39). Interpretation: This prospective trial shows that SM+ is more effective than SM when repeated therapeutic maneuvers are performed but not when a single maneuver is performed. It also supports the hypothesis of the biophysical model: overextension of the head during step 2 brings the clot of otoconia beyond the vertex of the canal, which increases the effectivity. Classification of Evidence: This study provides Class I evidence that SM+ is superior to SM for multiple treatment maneuvers of pcBPPVcan.